Meteorological observations at Syowa Station in 1985 by the 26th Japanese Antarctic Research Expedition - Shigemi Meshida; Shizuo Fukusawa; Takashi Shimamoto; Masao Wakabayashi (National Institute of Polar Research, 1989)
This paper describes the results of meteorological observations at Syowa Station, from February 1,1985 to January 31,1986,carried out by Meteorological Observation Team of the 26th Japanese Antarctic Research Expedition. Observation items and methods are almost the same as in 1984. Newly, observation by sunphotometer has started, and helium gas was used for all aerological observation balloons instead of hydrogen gas. Remarkable characteristics are as follows : 1) In a period without winter, monthly means of total amount of ozone recorded the lowest values. Especially, the value was low in September and October, and 176 (m atm-cm) observed on October 11,1985 was the lowest since observation had started. 2) Annual mean temperature above 100-mb height in the stratosphere has been tending lower from 1981,and recorded the lowest value in 1985. 3) Sea ice around the Ongul Islands almost flowed away during March to May. 4) Minimum temperature of Mizuho Station, -61.9℃ (July 16,1985), was the lowest value since observation had started.